Misplaced Gratitude and the Ethics of Oppression. (October 2016) - May Schott, Robin
Abstract: This essay examines Claudia Card's notion of misplaced gratitude, which she explores in one of her last papers, "Gratitude to the Decent Rescuer." Whereas typically philosophers have been interested in the problems of the failures to honor obligations of gratitude, Card is more interested in the opposite fault of misplaced gratitude. Her interest reflects her social indignation and her fundamental commitment to opposing oppression, exploitation, and injustice in all its forms. The phenomenon of misplaced gratitude becomes visible from this perspective, where one catches sight of what oppression does to people. The essay looks at the question, What does Card's analysis of misplaced gratitude tell us about her own philosophical methods and contributions? It discusses her engagement with both care ethics and Beauvoir's phenomenology of oppression to clarify the centrality of misplaced gratitude for Card's work in developing an ethics of oppression.